Mood and Modality in Lohorung - Rai, Diwas (Kirat Pragya किरात प्रज्ञा, 2026)
This study examines the mood and modality of Lohorung, a Rai Kirati language of the Tibeto-Burman language family spoken in the Sangkhuwasabha District, the eastern part of Nepal. Lohorung expresses mood and modality through morphological marking, although particles also play a vital role in conveying and refining semantic distinctions. The study examines four moods: (viz., indicative, imperative, interrogative, and optative). The indicative mood is examined as realis, where the particle states factuality, while copular verbs such as hɔ and ʈsuːk also indicate factual events, with reinforcing degrees of certainty. The imperative mood is categorized as irrealis and is morphologically marked by that functions as a portmanteau marker, encoding both imperative force with second-person singular agreement. Interrogatives are distributed into two types (viz., polar (Yes/No) and Wh). Yes/No interrogatives are marked by the marker with falling intonation and with rising intonation and are regarded as realis, whereas lexical Wh-interrogatives are evaluated as irrealis. The optative mood, expressing wishes and desires, is characterized as irrealis and is marked by < –rɔ>, , and . Modality is divided into two types (viz., epistemic and evaluative types). The epistemic modality comprises probability, certainty, evidentiality, and negation, while the evaluative modality encompasses ability and obligation. The marker indicates probability, and the particle hints certainty. Negation is morphologically expressed through prefixes (viz. , in past contexts; in imperatives) and the suffix in non-past contexts. The verb heː denotes ability (realized as hi in serial verb construction), while lɛːk expresses obligation. The findings prove the complicated interaction between morphology and particles in encoding mood and modality in Lohorung.